Prediction of coal dust particle size after spraying dust reduction in roadway based on orthogonal experiment and regression analysis - Bingyou JIANG; Yuqian ZHANG; Changfei YU; Ben JI; Haoyu WANG; Zhuang LIU (Meitan kexue jishu)
In order to investigate the main factors affecting the effect of spray dust reduction on the particle size of coal dust after spray dust reduction, a quantitative mathematical model was obtained to characterize the quantitative relationship between the influencing factors and the particle size parameters of coal dust after spray dust reduction. Based on the comprehensive experimental platform for spray dust removal, orthogonal experiments and regression analysis methods were applied to study the change rule of coal dust characteristic particle size D90 after spray dust reduction under the effect of three factors, namely, spray frame distance from dust source, tunnel wind speed and nozzle water supply pressure, and correlation analysis was carried out on 25 groups of experimental results. The weight value of each influencing factor in the coal dust D90 after spray dust reduction was determined by the mean square variance decision making method. On this basis, combined with the weights of each influencing factor, a weighted-based multivariate nonlinear regression prediction model of coal dust D90 after spraying dust reduction was constructed, and its prediction results were compared and analyzed with those of the multivariate linear regression model. The results show that: the coal dust D90 after spray dust reduction decreases with the increase of the distance from the dust source to the spray frame, increases and then decreases with the increase of wind speed, and increases with the increase of water supply pressure, and there is a strong positive correlation between full dust, exhaled dust reduction efficiency and D90, the better the spray dust reduction effect, the larger the coal dust D90 after spray dust reduction; the weighting-based prediction model of coal dust D90 after dust spraying has higher accuracy and smaller error, and can accurately characterize the quantitative relationship between coal dust D90 after dust spraying and three influencing factors, namely, the distance of the spray frame from the dust source, the wind speed of the roadway, and the water supply pressure of the nozzle.